Development of the FORUM: a new patient and clinician reported outcome measure for forensic mental health services. Issue 9 (21st October 2022) - Ryland, Howard; Cook, Jonathan; Ferris, Rob; Markham, Sarah; Sales, Christian; Fitzpatrick, Raymond; Fazel, Seena
ABSTRACT: Forensic mental health services provide care to people in secure psychiatric hospitals and via specialised community teams. Such services are typically low volume and high cost, often highly restrictive and average duration of inpatient care prior to discharge is long. Measuring outcomes of care is important to safeguard patients and the public, monitor progress, inform treatment plans and assist in service evaluation and planning. We describe the development in England of a new outcome measure for forensic mental health services. Patient interviews and multi-stakeholder focus groups were held to elicit key concepts. Thematic analysis was used to develop an outcomes framework. Fifteen patients participated in the interviews and 48 stakeholders in the focus groups. Six domains were identified in thematic analysis: 'about me, my quality of life, my health, my safety and risk, my life skills and my progress'. Sixty-two stakeholders participated in the first round of the Delphi process, and 49 completed round two. Eight of the top fifteen outcomes were shared between patients/carers and professionals. Based on these results, a new outcome measure, the FORensic oUtcome Measure (FORUM), was developed including both a patient reported and clinician reported measure. Further assessment of the FORUM's use to track patients' progress over time, and facilitate shared decision-making and care planning, is required.